Sydney Chapman: A Biographical Sketch Based on the Book “Chapman Eighty, From His Friends” - Syun‐Ichi Akasofu (Perspectives of Earth and Space Scientists)
Abstract This is a brief biographical sketch of Sydney Chapman, who was one of the greatest geophysicists in the world during the 20th century and also a pioneer in space physics. It is based on the book “Chapman eighty, from his friends,” together with a few notes by the author. In his early days, Chapman devoted his study on the transport property of gases and wrote “The Mathematical Theory of Non‐Uniform Gases” with T. G. Cowling. In the field of geophysics (geomagnetism, ionospheric physics, and auroral physics), Chapman made fundamental contributions in each field, on the basis of rigorous mathematical physics and deep insight. Chapman also wrote the book “Geomagnetism” with J. Bartels. These efforts helped establish the foundation of a new field, space physics. Chapman was instrumental and effective in coordinating various international scientific organizations, serving as presidents for the International Union of Geodesy and Geophysics (IUGG), the International Association of Geomagnetism and Aeronomy (IAGA), and the International Geophysical Year (IGY). Present advance in geophysical sciences owes greatly his devotion and accomplishments.